Comparison of Carboplatin With 5-Fluorouracil vs. Cisplatin as Concomitant Chemoradiotherapy for Locally Advanced Head and Neck Squamous Cell Carcinoma - Hanemaaijer, Saskia H.; Kok, Iris C.; Fehrmann, Rudolf S. N.; van der Vegt, Bert; Gietema, Jourik A.; Plaat, Boudewijn E. C.; van Vugt, Marcel A. T. M.; Vergeer, Marije R.; Leemans, C. René; Langendijk, Johannes A.; Voortman, Jens; Buter, Jan; et al. (Frontiers in Oncology, 2020)
Background: Chemoradiotherapy (CRT) including three cycles of cisplatin is considered the standard of care for locally advanced head and neck squamous cell carcinoma (LA-HNSCC). However, around one-third of the patients cannot complete cisplatin due to toxicity. Carboplatin plus 5-fluorouracil (carbo-5FU) is another accepted treatment option with a different toxicity profile. We compared tolerability and efficacy of concomitant carbo-5FU and cisplatin. Material and Methods: We conducted a retrospective analysis of LA-HNSCC patients treated with CRT in two Dutch cancer centers between 2007 and 2016. All patients received intensity-modulated radiotherapy. One center routinely administered carboplatin 300-350 mg/m2 at day 1, 22 and 43 followed by 5FU 600mg/m2/day for 96 hours. The other center used cisplatin 100 mg/m2 at day 1, 22 and 43. The primary endpoint of this study was chemotherapy completion rate. Secondary endpoints included overall survival (OS), disease-free survival (DFS), locoregional control (LRC) and distant metastasis free interval (DMFS), toxicity and unplanned admissions. Results: In the carbo-5FU cohort (n = 211), 60.2% of the patients completed chemotherapy versus 76.7% (p <0.001) of the patients in the cisplatin cohort (n = 223). Univariate analysis showed a higher risk of death in the carbo-5FU cohort (HR 1.53, 95% CI, 1.09 - 2.14, p = 0.01) with a three-year OS of 65.4% versus 76.5% for cisplatin. OS was independently associated with T and N stage and p16 status, but not with chemotherapy regimen (HR 1.08. 95% CI, 0.76 - 1.55, p = 0.65). Three-year DFS was 70.0% for carbo-5FU versus 78.6% for cisplatin (HR = 1.37, 95% CI, 0.93 - 2.01, p = 0.05). Similar outcome was observed for both LRC (HR 1.27, 95% CI 0.74 - 2.09, p = 0.4) and DMFS (HR 1.08, 95% CI 0.62 - 1.90, p = 0.77). The risk of discontinuation for chemotherapy-associated toxicity was higher in the carbo-5FU cohort than in the cisplatin cohort (relative risk = 1.69). Conclusion: LA-HNSCC patients treated with concomitant carbo-5FU completed chemotherapy less frequently than patients treated with cisplatin. Treatment regimen was not an independent prognostic factor for OS.